Great Indian Economists vol.7 Their creative vision for socio-economic development -Professor V.K.R.V.Rao - Das, Debendra Kumar (ed) (New Delhi Deep & Deep Publications, 2004)
Professor V.K.R.V.Rao - life sketch and economic philosophy